Ultrasound‐mediated delivery of flexibility‐tunable polymer drug conjugates for treating glioblastoma. Issue 2 (19th November 2022) - Sun, Tao; Krishnan, Vinu; Pan, Daniel C.; Filippov, Sergey K.; Ravid, Sagi; Sarode, Apoorva; Kim, Jayoung; Zhang, Yongzhi; Power, Chanikarn; Aday, Sezin; Guo, Junling; Karp, Jeffrey M.; et al.
Abstract: Effective chemotherapy delivery for glioblastoma multiforme (GBM) is limited by drug transport across the blood–brain barrier and poor efficacy of single agents. Polymer–drug conjugates can be used to deliver drug combinations with a ratiometric dosing. However, the behaviors and effectiveness of this system have never been well investigated in GBM models. Here, we report flexible conjugates of hyaluronic acid (HA) with camptothecin (CPT) and doxorubicin (DOX) delivered into the brain using focused ultrasound (FUS). In vitro toxicity assays reveal that DOX‐CPT exhibited synergistic action against GBM in a ratio‐dependent manner when delivered as HA conjugates. FUS is employed to improve penetration of DOX‐HA‐CPT conjugates into the brain in vivo in a murine GBM model. Small‐angle x‐ray scattering characterizations of the conjugates show that the DOX:CPT ratio affects the polymer chain flexibility. Conjugates with the highest flexibility yield the highest efficacy in treating mouse GBM in vivo. Our results demonstrate the association of FUS‐enhanced delivery of combination chemotherapy and the drug‐ratio‐dependent flexibility of the HA conjugates. Drug ratio in the polymer nanocomplex may thus be employed as a key factor to modulate FUS drug delivery efficiency via controlling the polymer flexibility. Our characterizations also highlight the significance of understanding the flexibility of drug carriers in ultrasound‐mediated drug delivery systems.